Respostas fisiológicas e bioquímicas de plantas jovens de arroz tratadas com silício submetidas ao estresse salino - Silva, Maria Lílian dos Santos (2015)
Beneficial effects of fertilization with silicon have been observed in several plant species, especially when they are subjected to biotic and abiotic stress. Among the abiotic factors, the salinity of the soil has constituted one of the most serious problems for irrigated agriculture in many parts of the world. This studo aimed to analyze the influence of silicon in rice plants subjected to increasing levels of salinity. Plants were grown in nutrient solution containing NaCl and Si levels corresponding in a greenhouse of the Department of Biochemistry and Molecular Biology of the Federal University of Ceará. The experimental design was completely randomized with four replications, in a factorial 3 x 3, being used three levels of NaCl (0, 50 and 100 mM) and three levels of Si (0, 2 and 4.0 mM). After 15 and 30 days of the beginning of the application of the treatments analyzed: growth, gas exchange, chlorophyll and carotenoids, organic and inorganic solutes analysis and the activity of enzymes in oxidative stress (SOD, CAT, APX and GPX). Salinity reduced all growth variables analyzed, however the silicon was able to increase them as much in control as conditions in salt stress conditions. Si 4 mM gave significant increases in photosynthesis and chlorophyll b parameters of plants subjected to 100 mM NaCl in the two times of exposure to salt. The Na + ions, Cl- were increased by salt stress in leaves and roots, while K+ and NO3- ions were reduced, being only 15 days NO3- stress. However, plants growing in Si - to 2 mM had the lowest levels of Cl in the leaves under the two levels of salt stress and the two exposure times. The higher concentration of silicon in the middle of the reduced levels of Na + only 30 days sheets when subjected to 100 mM NaCl and favored NO3- increase in stressed plants. Overall the Si increased the proline content in plants under salt stress at 15 days of exposure to salt and provided increases in soluble proteins. The enzymatic antioxidant system of plants supplied with Si was more efficient, especially with the action of enzymes CAT, APX and GPX, contributing to the resistance of plants to abiotic stresses. Supplementation with Si was able to mitigate the effects of the salinity in rice plants.